Spiral-driven accretion in protoplanetary discs: III. Tridimensional simulations - Hennebelle, Patrick; Lesur, Geoffroy; Fromang, Sébastien (Astronomy and astrophysics (Berlin), 2017)
Context. Understanding how accretion proceeds in proto-planetary discs, and more generally, understanding their dynamics, is a crucial questions that needs to be answered to explain the conditions in which planets form. Aims. The role that accretion of gas from the surrounding molecular cloud onto the disc may have on its structure needs to be quantified. Methods. We performed tridimensional simulations using the Cartesian AMR code RAMSES of an accretion disc that is subject to infalling material. Results. For the aspect ratio of H / R ≃ 0.15 and disc mass M d ≃ 10 -2 M ⊙ used in our study, we find that for typical accretion rates of the order of a few 10 -7 M ⊙ yr -1 , values of the α parameter as high as a few 10 -3 are inferred. The mass that is accreted in the inner part of the disc is typically at least 50% of the total mass that has been accreted onto the disc. Conclusions. Our results suggest that external accretion of gas at moderate values onto circumstellar discs may trigger prominent spiral arms that are reminiscent of recent observations made with various instruments, and may lead to significant transport through the disc. If confirmed from observational studies, such accretion may therefore influence disc evolution.